2010
DOI: 10.5897/ajb09.1282
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi improve the growth of olive trees and their resistance to transplantation stress

Abstract: Two native Algerian mycorrhizal fungi (Glomus mosseae and Glomus intraradices) were tested for their effect on the growth of micropropagated olive tree (Olea europaea L.). The effect of inoculation of plantlets with G. mosseae was also compared with chemical fertilization using osmocote. Specific molecular techniques were then used to detect the presence of the two fungi. Highly significant increases in growth were evident for inoculated plants compared with uninoculated ones. For a slightly lower shoot growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 33 publications
0
1
1
1
Order By: Relevance
“…The positive effect of inoculation could be also explained by the fact that these microorganisms are adapted to the pedoclimatic conditions of the environment. In fact, some studies have shown that inoculation can only be effective when the microorganisms are adapted to the environment abiotic conditions (Meddad-Hamza et al, 2010). Our results contrast those of Diatta et al (2013) who did not have a positive impact of inoculation on sesame in the natural environment due to presence of the native microflora.…”
Section: Direct Seedingcontrasting
confidence: 88%
“…The positive effect of inoculation could be also explained by the fact that these microorganisms are adapted to the pedoclimatic conditions of the environment. In fact, some studies have shown that inoculation can only be effective when the microorganisms are adapted to the environment abiotic conditions (Meddad-Hamza et al, 2010). Our results contrast those of Diatta et al (2013) who did not have a positive impact of inoculation on sesame in the natural environment due to presence of the native microflora.…”
Section: Direct Seedingcontrasting
confidence: 88%
“…Semelhante ao observado neste trabalho, Meddad-Hamza et al (2010) verificaram que maior taxa de colonização micorrízica em plantas de oliveira (Olea europaea L.) não resultou em maior eficiência na promoção do crescimento vegetal, concluindo que o sucesso da utilização de FMA no processo de aclimatização não depende exclusivamente do percentual de colonização micorrízica, mas da eficiência do fungo. Da mesma forma, Thonar et al (2011) Melo et al 2003), inclusive durante a aclimatização (Yano- Melo et al 1999, Oliveira et al 2010, Oliveira et al 2011.…”
Section: Resultsunclassified
“…Several benefits of AMF have been reported including improved plant survival and acclimatization, increased growth and nutrient uptake (especially P, Zn, Mn, Mg, Cu, K, and N), increased crop yields (Estaun et al, 2002; Wang et al, 2008; Kapulnik et al, 2010; Ortas, 2010; Kavoo-Mwangi et al, 2013) and improved water use efficiency (WUE; Auge, 2001). These have been reported for plants and crops like olive (Porras-Soriano et al, 2010), banana (Kavoo-Mwangi et al, 2013, 2014), turmeric (Radhika and Rodrigues, 2010) and cassava (Ceballos et al, 2013), and sweet potato (Abdel-Razzak et al, 2013). …”
Section: Introductionmentioning
confidence: 80%